PENGARUH RETURN ON ASSET (ROA), RETURN ON EQUITY (ROE) DAN NET PROFIT MARGIN (NPM) TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2018-2022 - Anggraini, Dewi; Iskandar, Eddy; Amalia, Mekar Meilisa (UNIVERSITAS DHARMAWANGSA, 2024)
The aim of this empirical research is to find and analyze the relationship between Return On Assets (ROA), Return On Equity (ROE), and Net Profit Margin (NPM) with business profit growth in banking companies listed on the Indonesia Stock Exchange (BEI) from 2018 to 2022. This research looked at the complete financial reports of 47 banking companies. A total of 13 companies met the purposive sampling criteria. Data analysis was carried out using descriptive statistics, classical assumption tests, multiple linear regression, and coefficient of determination. The research results show that ROA does not have a significant or beneficial impact on profit growth. ROE and NPM do not have a positive and significant impact on profit growth. Meanwhile, profit growth is not influenced positively and significantly by ROA, ROE, or NPM.